2019
DOI: 10.1111/pops.12563
|View full text |Cite
|
Sign up to set email alerts
|

On the Psychological Function of Nationalistic “Whitelash”

Abstract: A noticeable feature of the political discourse accompanying the rise of nationalism in white‐majority countries is that white people fare worse than other ethnic groups in their societies. However, it is unclear based on the extant literature why group‐based relative deprivation (GRD) would correlate with majority‐group nationalism. Here, we propose that the psychological function of nationalism for majority‐group members lies in its ability to assuage the negative feelings arising from GRD. Accordingly, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…In this sense, because disputes over racial discrimination are perceived as a zero-sum "game" by Whites (Norton & Sommers, 2011), systemjustifying members of the advantaged group may engage in competitive victimhood by claiming reverse discrimination, thereby buttressing their position within the status hierarchy and reinforcing the status quo (see Noor et al, 2012). Because maintaining the status quo furthers the group interests of the advantaged, system-justifying beliefs may reflect an identity compensation strategy for the advantaged (see Sengupta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, because disputes over racial discrimination are perceived as a zero-sum "game" by Whites (Norton & Sommers, 2011), systemjustifying members of the advantaged group may engage in competitive victimhood by claiming reverse discrimination, thereby buttressing their position within the status hierarchy and reinforcing the status quo (see Noor et al, 2012). Because maintaining the status quo furthers the group interests of the advantaged, system-justifying beliefs may reflect an identity compensation strategy for the advantaged (see Sengupta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, from an attributional approach (e.g., Olson & Hafer, 2001), system-justifying beliefs should reduce perceptions of unfairness by minimizing external attributions of negative and unfavorable outcomes (see also Weiner et al, 2011). Also, status-specific processes including positive group distinctiveness or social dominance among the advantaged (and attributions of self-blame among the disadvantaged) should be investigated (see Sengupta et al, 2019). Such research could help to uncover the myriad ways in which SJ serves the interests of the advantaged, yet undermines the interests of the disadvantaged.…”
Section: Discussionmentioning
confidence: 99%
“…This can be the case even if the group is not objectively disadvantaged. For example, national collective narcissism was higher among those Americans who perceived they are being worse off than immigrants (Marchlewska et al, 2018; see also Sengupta, Osborne, & Sibley, 2019).…”
Section: The Roots Of Collective Narcissismmentioning
confidence: 99%
“…The present research offers a novel context through which to view research on the way people react to demographic changes and exposure to information conveying increasing diversity. Recall that negative reactions to these implicate zero-sum beliefs, perceived group-based deprivation, and conservative ideology, and these may be especially strong among White Americans (Craig & Richeson, 2017;See Craig, Rucker, & Richeson, 2018;Wilkins et al, 2018;Wilkins et al, 2017;Van Assche, Roets, Van Hiel, & Dhont, 2019;Sengupta, Osborne, & Sibley, 2019). The findings reported here offer that there are existential and motivational constructs that may hold similar relevance to these processes.…”
Section: Implications For Diversitymentioning
confidence: 67%
“…For instance, a recent review of the literature suggests that rather than leading to shifts in attitudes, exposure to diversity simply aggravates existing negative intergroup attitudes among those who endorse right-wing views (see Van Assche, Roets, Van Hiel, & Dhont, 2019). Building on these findings, Sengupta, Osborne, and Sibley (2019) showed that feelings of group-based relative deprivation (which often result from zero-sum beliefs and perceptions of increasing diversity) contribute to nationalistic ideology, which in turn, predicts higher subjective well-being. Further, experimental research shows that exposure to diversity information causes people to endorse more conservative ideology (Craig & Richeson, 2014), and promotes group-based conventionalism (Dieckmann, Steffens, & Methener, 2018;often implicated in right-wing views, Feldman, 2003).…”
Section: Diversity Inclusivity and American Identitymentioning
confidence: 95%